The moderating role of reward on the impact of academic supervision and multitasking in enhancing teachers’s job satisfaction - Widodo; Agus Wahyudin; Masrukhi; Widiyanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Rewards can enhance job satisfaction among teachers by addressing their individual needs and preferences. Factors like degree levels, self-motivation, and support for students influence teachers' competency and job satisfaction.